Denitrification workshop planned - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
The International Society of Soil Science is to hold a workshop on denitrification in soils, the rhizasphere and aquifers, in Giessen, Germany, from March 17 to 19,1989. This IS to be an international meeting for experts in this field. At present...